Formation of Future Philologists’ Professional Competence in the Aspect of Activity Approach - Danylyuk, Serhiy (Pedagogical Discourse, 2011)
The article deals with the highlighting of the formation of future philologists’ professional competence in the light of an axiological approach. The usage of this approach in the process of formation of the professional competence of students of linguistic specialties is conditioned by the need of modernization of education and development of new strategies of its development as well as implementation of changes in the strategies of higher education. Peculiarities of basic teaching principles in shaping future philologists’ professional competence are studied in the article.